THE INFLUENCE OF LEADERSHIP STYLE AND WORK MOTIVATION ON TEACHER PERFORMANCE AT MIFTAHUL JANNAH ISLAMIC ELEMENTARY SCHOOL (MADRASAH IBTIDAIYAH), PURWAKARTA - Jejen Zaenuddin; Aswin Naldi Sahim; Nurmansyah (STMIK Indonesia Banda Aceh, 2026)
This study aims to analyze the influence of leadership style and work motivation on the performance of teachers at Miftahul Jannah Islamic Elementary School (Madrasah Ibtidaiyah), Purwakarta. The research is grounded in the importance of leadership style and work motivation for teacher performance at this institution. A quantitative approach was employed, combining descriptive and verificative methods. Data were collected through questionnaires administered to 35 teachers at Miftahul Jannah Islamic Elementary School, Purwakarta, and analyzed using multiple linear regression. The results indicate that both leadership style and motivation have a positive and significant effect on teacher performance, both partially and simultaneously. The study concludes that leadership style and work motivation are essential for enhancing teacher performance at Miftahul Jannah Islamic Elementary School, Purwakarta.